Performance Measure Manipulation* - DEMSKI, JOEL S. (Contemporary Accounting Research, 1998)
A two‐period model in which communication restrictions preclude the usual revelation representation is analyzed, and the communication policies take on the appearance of “income smoothing.” The driving force is the information content of the “smoothed” or manipulated series, relative to its counterpart were manipulation not possible. Various possibilities arise, depending on the underlying stochastic structure: performance measure manipulation might be socially efficient, or not; and when it is best to invite and motivate this manipulation, the optimal policy itself can take on a variety of forms.